(untitled) (European Journal of Education and Psychology, 2010)
To correct social setting, peers are key actors, both as a socio-psycho-emotional and behavioral students since figures is similar perspectives and promote the acquisition of social skills, friendships, adapting to new social roles etc. Anxiety, likelihood of action and defense of the rights themselves interfere with students with learning disabilities because they lack social skills not only to perceive and understand the logical relationships, but also to prevent and choose the appropriate behavior in social situations. Therefore, the purpose of this communication is to analyze the different variables of social skills in students with learning disabilities. The sample for carrying out the study corresponds to 193 students from 4th to 6th year of primary education of different type (children with and without learning disabilities and students with attention deficit hyperactivity disorder (ADHD). The results obtained show an emotional disadvantage in relation to LD and ADHD students compared to students without learning disabililties.